Dwindling Social Prosperity and Migratory Youths (Himalayan Journal of Sociology and Anthropology, 2014)
Migratory trend in Nepalese society is an ever growing trend. Nepalese have migrated abroad through different ways in different time like recruitment in army, as cheap manpower and now to pursue the foreign degrees. Whatsoever the excuses are, country is losing the skilled youths in present context jeopardizing the socio economic development of the country. This study investigates the influencing social factors that motivate educated youth to leave their country in the name of education. Similarly this study has also sensed the integrity of youth towards their own country. It should help concerned scholars to have a bit more concern about their role to choreograph the structure and function that favour the social welfare and development. Youths attempting to enroll themselves for IELTS test in British Council were surveyed and this study adopted an exploratory and descriptive research design. It is found that youths are tempted to go abroad with the motive to settle in there as the native structural and functional aspects of the society are not found justifiable. Moreover youths have placed the foreign degrees in higher priority to access in a decent job anywhere. Lastly the study has concluded that the execution of the policies in every field should not be manipulated instead fair competition and strict bureaucracy in the system must be practiced. However the trend of employment in foreign must also be accepted with dignity. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10731 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 211-220